Convergent morphology in alpinieae (Zingiberaceae): Recircumscribing amomum as a monophyletic genus (2018)
The tropical ginger genus Amomum (Zingiberaceae) has always posed challenges for classification based on morphological characters. Previous molecular phylogenetic studies showed Amomum to be paraphyletic but limited sampling and absence of the data of the type Amomum subulatum made it impossible to resolve the paraphyly and make nomenclatural changes. Here, Amomum is further investigated in a multi-marker phylogenetic framework using matK and nrITS including multiple accessions of the type, the genus Elettaria and additional accessions of Amomum, Alpinia, Elettariopsis, Geocharis, Geostachys and Hornstedtia. Amomum is shown to consist of nine clades and Alpinia of six. The genera Elettaria, Elettariopsis, Plagiostachys, and species in Hornstedtia are nested within these clades. Morphological studies of species previously subsumed in Amomum support recognition of new genera that correspond to well-delimited clades in the phylogenetic framework presented here. Recircumscription of the paraphyletic genus Amomum facilitates identification and creates nomenclatural stability. Three genera, Conamomum, Meistera and Wurfbainia, are resurrected, and three new genera Epiamomum, Lanxangia and Sundamomum are described, together with a key to the genera and a nomenclatural synopsis placing 384 specific names (incl. all synonyms) into the new generic framework. Of these 129 represent new combinations and 3 are replacement names. Types of Geocharis and Geostachys are designated. Further studies and specific sampling will be needed to resolve other branches of Alpinioideae containing other polyphyletic genera. © International Association for Plant Taxonomy (IAPT) 2018, all rights reserved.